The impact of a gamified approach on vocabulary learning and vocabulary self-efficacy: evidence from a chilean primary EFL school - Marco Cancino; Camila Viguera (Revista de Lingüística y Lenguas Aplicadas)
Although many studies addressing gamified approaches have documented the performance and perceptions of adult EFL learners, little research has been conducted with younger students and with a focus on specific linguistic components. Therefore, the present study assessed the impact of a gamified approach involving the use of Kahoot! on the vocabulary learning and vocabulary self-efficacy of 122 primary EFL school learners. A quasi-experimental design was applied where participants were divided into an experimental group (n = 57) that was exposed to vocabulary learning through Kahoot! and a control group (n = 65) that received traditional coursebook instruction. Ten target words were assessed through a vocabulary learning post-test, while vocabulary self-efficacy was evaluated through a questionnaire. Results revealed that both groups performed equally well regarding lexical gains, and that students in the experimental group significantly increased their vocabulary self-efficacy when compared to the control group. Pedagogical implications are discussed.